LEARNING TO WRITE POETRY TO GROW STUDENT CHARACTER EDUCATION THROUGH GENIUS LEARNING - Martin Indah (Yayasan Citra Dharma Cindekia, 2020)
The purpose of this study was to determine the assessment of writing poetry to foster student character education after the application of genius learning. The method used is descriptive quantitative. The population used was high grade students consisting of grades 4, 5, and 6 in SD Negeri Medalem, Modo District, Lamongand Regency with a sample of 30 students consisting of 15 male students aged 10-12 years and 15 female students aged 10-12 years. . This research was conducted from 4- 22 February 2020. The test instrument was used in the form of a description given after the learning was carried out. The question grid, description questions, and rubrics had previously been validated by experts and practitioners before the questions were tested out to the experimental class students. Time to work was 30 minutes. There are 4 assessments in determining the assessment of learning to write, namely fostering a love for writing in students, developing students 'writing skills, fostering students' creative spirit to write, and developing student character. The results of the research before the genius learning were carried out, there were 6 or 20% students, after the genius learning was carried out, students who completed it became 27 or 90% of the population. The results of the assessment of writing poetry to foster student character education after the application of genius learning is significantly complete.